BANK SYARIAH : Antara Labelisasi dan Pemberdayaan Ekonomi Masyarakat - Mansur Mansur (Ulumuna: Jurnal Studi Keilsman, 2018)
The concept of Syariah Bank empowerment of the community's economy through its products such as: Mudharabah, Musyarakah, Murabahah, Kafala, and others, is a banking service that reflects its concern for improving the economy and welfare of the poor. While the weaknesses in the internal field such as inadequate institutional factors, and external factors, such as the readiness of the community to accept the presence of the Syariah Bank, are welcome in the National banking system, provided they are accompanied by high progression. The labeling of "syariah" in a bank is intended as a banking system in accordance with Islamic Law (Syariah) which is rahmatan lil ‘alamin. While the influence of labeling in the context of community economic empowerment is not so significant. Because, there is more needed is the quality of service and ease of access. In addition, the formalization of religion has the potential to be misused by its role to be so particular. In fact, for non-Muslims it is considered a political-economic institution founded on religious sentiments. Thus, the position of Bank Syariah is still ambiguous between community economic empowerment or formalization of religion.